2011
DOI: 10.1002/mrm.22922
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time functional MRI using pseudo‐continuous arterial spin labeling

Abstract: The first implementation of real-time acquisition and analysis of arterial spin labeling-based functional magnetic resonance imaging time series is presented in this article. The implementation uses a pseudo-continuous labeling scheme followed by a spiral k-space acquisition trajectory. Real-time reconstruction of the images, preprocessing, and regression analysis of the functional magnetic resonance imaging data were implemented on a laptop computer interfaced with the MRI scanner. The method allows the user … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…This study presents promising results that promote the use of machine‐learning techniques for brain‐state classification of images acquired by using the AVAST technique. This technique might be used for dynamic fMRI experiments and real‐time brain‐state classification studies as in Hernandez‐Garcia, Jahanian, Greenwald, Zubieta, & Peltier ().…”
Section: Discussionmentioning
confidence: 99%
“…This study presents promising results that promote the use of machine‐learning techniques for brain‐state classification of images acquired by using the AVAST technique. This technique might be used for dynamic fMRI experiments and real‐time brain‐state classification studies as in Hernandez‐Garcia, Jahanian, Greenwald, Zubieta, & Peltier ().…”
Section: Discussionmentioning
confidence: 99%
“…Although EPI is sensitive to susceptibility artifacts by air space in HNT, TBF was measured successfully using a small matrix (80 × 80 in 23 × 23 cm FOV), a wide bandwidth of 2303 Hz/pixel, and a short TE of 24 msec, to minimize susceptibility artifact. Recently, several studies using readout of the 3D spiral FSE technique have been reported . This novel technique might be applied to HNT with less susceptibility artifact.…”
Section: Discussionmentioning
confidence: 99%
“…It has poorer temporal resolution than EPI as a result but the advantages of a physiological and clinically meaningful outcome measure in rCBF and a true baseline. Real-time ASL (rtASL) has recently been reported (Hernandez-Garcia et al, 2011). Although currently the signal-to-noise ratio is not as good as EPI and there are still issues with selecting the optimal feedback region, the future for rtASL is promising due to its inherent advantages over BOLD signal related methods (presentation by Várkuti).…”
Section: Where Is the Future Of Rtfmri Neurofeedback?mentioning
confidence: 99%